Comparison study between the treatment of Hepatitis C virus with (peg-interferon, ribavirin, silymarin) and (peg-interferon, ribavirin) in Baghdad teaching hospital. - Al-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Infection with Hepatitis C virus (HCV) is a major cause of chronic liver disease, WHO estimated that about 170 million people are infected with Hepatitic C virus, Silymarin (Legalon) have been recently shown to be effective in treatment of Hepatitic C virus infection. Objectives: The effectiveness of Legalon (Silymarin) on viral load in patients with Hepatitic C virus infection. Patients and methods: A prospective case – control study included 400 patients with Hepatitis C virus infection. 200 patients (group A) were treated with (peg-interferon, ribavirin, silymarin) the other 200 patients (group B) were treated with (peg-interferon, ribavirin) . only G1 & G4 genotypes were included , viral load were assessed initially and after 3 months in patients with positive viral load. Results: Viral load follow in group A, Hepatitis C Viral load was reported in 150 cases giving a response rate of 75% while in the 200 cases of group B the response was reported in 110 giving an overall response rate 55% , this indicate that cases in group A had a significant higher response rate than those in group B. Conclusion: Patients taking Silymarin (420 mg/day) for 3 months showed a decrease in viral load, effectiveness of silymarin was more in Genotype 1 than in the Genotype 4, the response was better in low viral load patients ( less than 600000 IU/ml).